An Analysis of Students’ Anxiety in Speaking Class of English Department, Universitas Putra Indonesia YPTK, Padang - Suparmi, Suparmi - (TELL - US JOURNAL, 2018)
ABSTRACK                                                                                      The aim of this research is to know the type ofanxiety encountered by students in speaking class and toknow the dominant factor of anxiety in speaking class. The type of this research is descriptive research. The respondent of this research are the English Department students of UPI YPTK Padang. Total respondent in this research are 26 students. In collecting the data, the researcher used questionnaire, interview and observation. First, the researcher distribute the questionnaire to the respondent, the questionnaire include 33 items based on the indicator about speaking anxiety. Based on the data from all instruments the researcher concluded that the domnant anxiety encountered by the students is State Anxiety that has high percentage from the other type of anxiety, that is 67%. Then, the dominant factor that influence on students spekaing anxiety is lack of preparation, they feel anxiety because lake of preparation, so they do not know what should be conveyed. Keywords: Speaking, Anxiety, Types of Anxiety, Factors of Anxiety